Clinical, Radiographic, Pathologic Characterization and Survival Outcomes of Nuclear Protein of the Testis Carcinoma. Issue 3 (May 2021) - Virarkar, Mayur; Mallery, Marcelle; Saleh, Mohammed; Ramani, Nisha S.; Morani, Ajaykumar C.; Bhosale, Priya
Abstract : Introduction: Nuclear protein of the testis (NUT) carcinoma (formerly NUT midline carcinoma) is an aggressive tumor with characteristic BRD4 - NUTM1 translocation and a poor prognosis. The primary objective of this study was to describe the clinical and radiologic features, treatment response, and survival of NUT carcinoma (NC). Materials and Methods: This retrospective single-center study was based on the review of medical records of NC patients with a specific genetic rearrangement or positive anti-NUT nuclear staining. Overall survival (OS) was analyzed according to primary tumor location. Results: This series of 22 patients had a mean age of 36.27 ± 2.68 years with 68% women and 32% men. The median age at diagnosis was 34 years (range, 17–55 years). The primary tumor was located in the chest (n = 12/22; 55%), head and neck (n = 9/22; 40%), and 1 patient had a renal tumor. About 68% (n = 15/22) patients presented with regional lymph nodal involvement and 77% (n = 17/22) had distant metastases. All the bone metastases were lytic (100%) with mixed lytic and sclerotic metastases in 5 patients. Only 18% (n = 4/22) of the patients showed response to treatment, with progression in the remaining 18 patients. The median OS was 7 months. The OS was significantly ( P = 0.024) more in patients with primary head and neck NC (n = 9; OS, 16 months) versus those with pulmonary and other locations (n = 13; OS, 6 months). Conclusions: Nuclear protein of the testis carcinoma is an aggressive disease refractory to conventional therapy. Imaging with the complementary use of computed tomography, magnetic resonance imaging, and positron emission tomography/computed tomography is important for staging, guiding management, assessing the treatment response, and surveillance.